2019
DOI: 10.1016/j.ssnmr.2019.04.008
|View full text |Cite
|
Sign up to set email alerts
|

DNP-NMR of surface hydrogen on silicon microparticles

Abstract: Dynamic nuclear polarization (DNP) enhanced nuclear magnetic resonance (NMR) offers a promising route to studying local atomic environments at the surface of both crystalline and amorphous materials. We take advantage of unpaired electrons due to defects close to the surface of the silicon microparticles to hyperpolarize adjacent 1 H nuclei. At 3.3 T and 4.2 K, we observe the presence of two proton peaks, each with a linewidth on the order of 5 kHz. Echo experiments indicate a homogeneous linewidth of ∼ 150 − … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 85 publications
0
4
0
Order By: Relevance
“…Figure b showed that chirped DNP significantly improved the enhancements for the two outer nuclear spin manifolds ( m I = ± 1) and blurred some of the sharper features associated with the central manifold ( m I = 0). The enhancement observed under modulation could be either due to the cross effect , or due to the introduction of a new mechanism, the integrated solid effect . Given the low microwave power and the rapid 5 kHz modulation rate, significantly faster than the electron T 1 , it is unlikely that the experiment satisfies the conditions necessary for achieving the integrated solid effect via frequency modulation. , Additionally the effect is not observed in the central ( m I = 0) manifold.…”
Section: Resultsmentioning
confidence: 99%
“…Figure b showed that chirped DNP significantly improved the enhancements for the two outer nuclear spin manifolds ( m I = ± 1) and blurred some of the sharper features associated with the central manifold ( m I = 0). The enhancement observed under modulation could be either due to the cross effect , or due to the introduction of a new mechanism, the integrated solid effect . Given the low microwave power and the rapid 5 kHz modulation rate, significantly faster than the electron T 1 , it is unlikely that the experiment satisfies the conditions necessary for achieving the integrated solid effect via frequency modulation. , Additionally the effect is not observed in the central ( m I = 0) manifold.…”
Section: Resultsmentioning
confidence: 99%
“…Here the outer lines are best fit using a combination of the CE and the OE or truncated CE. Figure 2(b) showed that chirped DNP significantly improved the enhancements for the two outer nuclear spin manifolds (m I = ±1), and blurred some of the sharper features associated with the central manifold (m I = 0) [66][67][68]. The enhancement observed under modulation could either be due to the cross effect [66,67] or due to the introduction of a new mechanism -the integrated solid effect [58].…”
Section: B Powdermentioning
confidence: 97%
“…This mechanism was observed for organic radicals with rather narrow EPR lines, for example, 1,3-bis(diphenylene)-2-phenylallyl (BDPA) (8), as well as for paramagnetic metal ions in highly symmetrical environments and with a half-filled electron shell, Mn(II), Gd(III), Cr(III), and Fe(III) (9)(10)(11)(12)(13)(14). Recently, SE was also observed with radicals generated by γ-irradiation (15) or present at the surface of the materials due to dangling bonds (16)(17)(18)(19)(20)(21).…”
Section: High-field Magic Angle Spinning Dnpmentioning
confidence: 99%
“…Nevertheless, due to its high sensitivity and generality, DNP-SENS is still the most used method for characterization of surfaces. DNP-SENS is a powerful tool to decipher the network of surface functionalities (71), assess interactions of dilute organic molecules on the surface (72), characterize coatings for membranes (73), determine the composition of cement (74), and study surfaces/interfaces in biomaterials research (18,(75)(76)(77). For instance, unreceptive 43 Ca nuclei (low γ and spin 7/2), an important element in biomaterials, can be detected at natural abundance, providing the unambiguous discrimination of core and surface calcium atoms in hydroxyapatite NPs (75).…”
Section: Surfaces and Interfacesmentioning
confidence: 99%